Marketing Internacional - Jurado Vinueza, Eduardo (2016)
International marketing it could be understood as knowledge and research exchange relationship has a partnership in legal, cultural and personal values different to those of the country of origin. However, there is a paradigm between Latin American search markets in Europe, Asia, North America. However, we have not focused on expanding markets in Latin America? This study gives an overview of how Latin America could become a world power if you generate your own ideas and landed their market conditions.